Nails in the wall: Catholic nuns in Reformation Germany - Leonard, Amy (Women in culture and society, 2005)
Life behind the walls : the establishment and growth of the Dominican convents -- From neighbor to neighbor : Reformation theories of the utility of the cloister -- The Reformation confronts the convents -- The ties that bind : nuns, families, and magistrates -- The empire strikes back : the Counter-Reformation in Strasbourg -- Nuns as whores : the closing of St. Nicholas-in-Undis